This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For integration by parts, let u = x 2 , d u = 2 x d x , d v = ( 1 + sin x ) 2 cos x d x . Then v = ∫ ( 1 + sin x ) 2 cos x d x . To quickly compute this antiderivative let w = 1 + sin x so d w = cos x d x so the integral becomes ∫ w 2 d w = − w − 1 = − 1 + sin x 1 . Then, the whole integral is equal to:
− 1 + sin x x 2 ∣ ∣ ∣ ∣ 0 2 π + ∫ 0 2 π 1 + sin x 2 x d x = − 8 π 2 + ∫ 0 2 π 1 + sin x 2 x d x . The remaining integral is very tricky but it can be turned into a known integral by playing with it a little:
1 + sin x = 1 + cos ( 2 π − x ) = 1 + cos ( 2 ( 4 π − 2 x ) ) = 2 cos 2 ( 4 π − 2 x ) so the integral is ∫ 0 2 π x sec 2 ( 4 π − 2 x ) d x . Finally, with the substitution u = 4 π − 2 x the integral becomes ∫ 0 4 π ( π − 4 u ) sec 2 u d u . This reduces the problem to computing ∫ sec 2 x d x and ∫ x sec 2 x d x which are standard integrals. In the end, it evaluates to lo g ( 4 ) so the solution is lo g ( 4 ) − 8 π 2 .
Problem Loading...
Note Loading...
Set Loading...
If we substitute y = sin x and then integrate by parts twice, we obtain ∫ 0 2 1 π ( 1 + sin x ) 2 x 2 cos x d x = ∫ 0 1 ( 1 + y ) 2 ( sin − 1 y ) 2 d y = [ − 1 + y ( sin − 1 y ) 2 ] 0 1 + 2 ∫ 0 1 1 − y 2 ( 1 + y ) sin − 1 y d y = − 8 1 π 2 + 2 ∫ 0 1 ( 1 − y ) 2 1 ( 1 + y ) 2 3 sin − 1 y d y = − 8 1 π 2 + 2 [ − sin − 1 y 1 + y 1 − y ] 0 1 + 2 ∫ 0 1 1 − y 2 1 1 + y 1 − y d y = 2 ∫ 0 1 1 + y d y − 8 1 π 2 = 2 ln 2 − 8 1 π 2 making the answer 0 . 1 5 2 5 9 3 8 1 1 .